Clinicopathological features of neoplasms with neuroendocrine differentiation occurring in the liver. Issue 7 (23rd November 2016) - Nomura, Yoriko; Nakashima, Osamu; Akiba, Jun; Ogasawara, Sachiko; Fukutomi, Shogo; Yamaguchi, Rin; Kusano, Hironori; Kage, Masayoshi; Okuda, Koji; Yano, Hirohisa
Abstract : Background/aims: We investigated the clinicopathological features of hepatic neuroendocrine tumours (NET) and neuroendocrine carcinoma (NEC), which remain largely unknown. Material and methods: We examined 1235 tumours from 1048 patients who had undergone curative hepatectomy for liver neoplasms at Kurume University Hospital. Pathological diagnoses were based on the 2010 WHO Classification of Tumours of the Digestive System. We performed immunostaining for hepatocyte markers (eg, hepatocyte paraffin (HepPar)-1), neuroendocrine markers (eg, chromogranin A (CGA)) and the proliferation marker (Ki-67). Results: There were four cases of NET G2 (0.38%) and five of hepatic malignant tumours with an NEC component (HNEC) (0.48%). HNEC cases were classified into three types, that is, transitional, intermediate and separate types, according to their histological and immunohistochemical features. In the former two types, the NEC component intermingled with the moderately to poorly differentiated hepatocellular carcinoma (HCC) component or intermediate component consisting of tumour cells showing the colocalisation of CGA and HepPar-1. In the separate type, the NEC and poorly differentiated HCC components were present separately, whereas the sarcomatous HCC component was detected in the vicinity of the NEC component. Ki-67 labelling indices of the NET G2, HCC and NEC components of HNEC were 6.8%, 14.9% and 58.9%, respectively. Conclusions: Primary hepatic NET and NEC are very rare tumours. The NEC component in HNEC showed high proliferative activity and influenced patient prognoses.